Yttrium-90 Radioembolization of Hepatic Metastases from Colorectal Cancer - Raval, Mihir; Bande, Dinesh; Pillai, Anil K.; Blaszkowsky, Lawrence S.; Ganguli, Suvranu; Beg, Muhammad S.; Kalva, Sanjeeva P. (Frontiers in Oncology, 2014)
Liver metastases from colorectal cancer (CRC) result in substantial morbidity and mortality. The primary treatment is systemic chemotherapy, and in selected patients, surgical resection; however, for patients who are not surgical candidates and/or fail systemic chemotherapy, liver-directed therapies are increasingly being utilized. Yttrium-90 (Y-90) microsphere therapy, also known as selective internal radiation therapy (SIRT) or radioembolization, has proven to be effective in terms of extending time to progression of disease and also providing survival benefit. This review focuses on the use of Y-90 microsphere therapy in the treatment of liver metastases from CRC, including a comprehensive review of published clinical trials and prospective studies conducted thus far. We review the methodology, outcomes and side effects of Y-90 microsphere therapy for metastatic CRC